Electrochemical Behaviour of N′-(p-toluenesulphonyl)-3-methyl-4-(4′-substituted arylhydrazono) pyrazolin-5-ones - V. Nagaraju; R. Sreenivasulu; P. Venkata Ramana (E-Journal of Chemistry)
The electrochemical behaviour of N′-(p-toluenesulphonyl)-3-methyl-4-(4′-substituted arylhydrazono) pyrazolin-5-ones has been investigated at dme and gc electrodes in buffer solutions of pH 2.0, 4.0, 6.0, 8.0 and 10.0 using dc polarography and cyclic voltammetry and coulometry. The compounds exhibit one well defined wave in the entire pH range of study. The process is irreversible and diffusion controlled. Controlled potential electrolysis indicates the involvement of four electrons in the reduction process. The effect of solvent, cations and anions, temperature and substitutents on the mechanism of reduction has been studied. Based on the results obtained the mechanism of reduction has been suggested.